THEORETICAL AND PRACTICAL ASPECTS OF DEVELOPMENT OF MILK PROCESSING INDUSTRY ENTERPRISES IN UZBEKISTAN - Khidirov Temur Kahramon o'g'li (American Journals, 2025)
This article describes the theoretical and practical aspects of the development of milk processing enterprises in Uzbekistan, scientific research conducted in this area, the relevance of the topic, the research methods used, practical problems, well-known brands of milk processing enterprises, the economic efficiency of the cluster system, and scientific issues related to innovative approaches to the development of milk processing enterprises.
Keywords: Milk processing enterprises, dairy industry, international experience, well-known brands, innovative solutions, practical problems, practical recommendations.